Worldwide Risk Analysis of Brain Tumours in Young Adults and Adolescents (Advances in Applied Biological Research, 2026)
In those under 20, the most common solid malignancies are brain tumours,  which account for most of cancer-related deaths. By gathering information from  institutional series, population-based studies, and case-control investigations  done all throughout the world, this review examines the weight, incidence, and  risk elements related with brain tumours in children and adolescents. Recent  epidemiological data from countries like Finland, Canada, the United States,  China, and Korea points to an annual incidence rate among young people ranging  from 3.5 to 5. 1 case per 100,000, with the highest rates observed among youngsters  aged 0 to 4. Among the most frequent tumour types are pilocytic astrocytoma,  medulloblastoma, ependymoma, aberrant teratoid/rhabdoid tumours, and  medulloblastoma. Studies show small local variations in the incidence of tumour  types; germ cell tumours are somewhat more common in Asian populations  and show a slight male bias. This review focuses on brain tumour in the young  population it’s a subject of growing medical and public health concern, this  evaluation emphasizes the essential need of continuous monitoring using national  cancer registries, molecular tumour profiling and improved early detection and  genetic testing initiatives. Understanding regional variances and risk factors for  paediatric brain tumour patients can inform future studies, focused prevention  campaigns, and improved survival and treatment outcomes. This information  was gathered from reputable websites such as DOAJ (directory of open access  journals), ERIC (education resources information centre), ScienceDirect, PubMed  and google scholar. The diagram has taken from biorander while the graph, pie  chart and flow chart are made in MS word.
Keywords: prenatal exposure, pilocytic astrocytoma, medulloblastoma, ependymoma, rhabdoid tumour, glioma.